PENGARUH MOTIVASI KERJA, KEPEMIMPINAN DAN SIKAP KERJA TERHADAP KINERJA PEGAWAI DINAS PEKERJAAN UMUM DAN PENATAAN RUANG KABUPATEN TAPANULI TENGAH - Binsar Joe Fanny Manurung; Ilham Ilham; Risky Ramadhan; Chandra Tua Situmorang; Rina Akhriati (Jurnal Prodi Fakultas Ekonomi-UISU, 2022)
Problem of this study how influence of job motivation on performance. How influence of leadership on performance. How influence ofwork attitude on performance. How influence job motivation, leadership and work attitude on performance. The purpose of this study to determine and analyze the effect of job motivation on performance. Determine and analyze the effect of leadership on performance. Determine and analyze the effect of work attitude on performance. Determine and analyze the effect of job motivation, leadership and work attitude on performance. Sample in the study is 48 employees. Data analysis techniques used in this study is descriptive analyze and multiple linear regression analysis. The results of the study indicate job motivation variable has a positive and significant effect on performance. Leadership variable has a positive and significant effect on performance. Work attitude variable has a positive and significant effect on performance. Job motivation, leadership and work attitude variable has a positive and significant effect on performance